A History of Radionuclide Studies in the UK 50th Anniversary of the British Nuclear Medicine Society - McCready, Ralph; Gnanasegaran, Gopinath; Bomanji, Jamshed B. (Springer International Publishing : Imprint: Springer, 2016)
The British Nuclear Medicine Society celebrates its 50th Anniversary with this booklet, which reflects the research of many of the pioneers in the use of radionuclides for the diagnosis and therapy of human disease. Since 1949 there have been remarkable advances in radionuclide techniques and imaging equipment: from the first devices "home-made" in the many physics departments throughout the UK, to the sophisticated multimodality imagers now in everyday use in Nuclear Medicine. The BNMS has been instrumental in promoting the use of radionuclide techniques in the investigation of pathology by supporting and providing education, research and guidelines on the optimum use of radiation to help patients. The future of Nuclear Medicine is bright, thanks to improved imaging resolution, new radiopharmaceuticals, and new diagnostic and therapeutic techniques and procedures.